Design of Product UMKM Ordering Application Using Firebase Realtime Database Based on Cload Computer - Novelan, Putra (Cattleya Darmaya Fortuna, 2024)
The growth of the UMKM (Micro, Small and Medium Enterprises) sector is increasingly rapid, encouraging the need for digital platforms to simplify the process of ordering UMKM products. This design proposes the development of an application for ordering UMKM products using the Firebase Realtime Database which is integrated with Cloud Computer. Firebase Realtime Database is used as real-time data storage, while Cloud Computer is used to run applications on a larger scale. This application makes it easy for customers to explore UMKM products, place orders, and track order status directly. Firebase Realtime Database enables automatic data updates, providing users with accurate and up-to-date information. Integration with Cloud Computer ensures the application can handle a large number of users, as well as increasing the reliability and performance of the application. The main features of the application include a list of UMKM products, shopping cart, ordering system, order status notifications, and transaction history. The security of customer data is guaranteed through encryption applied to communications between the application and the Firebase Realtime Database. By adopting Firebase Realtime Database and Cloud Computer technology, it is hoped that this application can provide an efficient shopping experience and advance the UMKM sector in utilizing digital technology. This design creates the basis for further application development that can increase customer engagement and expand the market for UMKM